Hemophagocytic lymphohistiocytosis/macrophage activation syndrome (HLH/MAS) following treatment with tisagenlecleucel. Issue 1 (7th January 2022) - Martín‐Rojas, Reyes Maria; Gómez‐Centurión, Ignacio; Bailén, Rebeca; Bastos, Mariana; Diaz‐Crespo, Francisco; Carbonell, Diego; Correa‐Rocha, Rafael; Pion, Marjorie; Muñoz, Cristina; Sancho, Milagros; Gómez Fernández, Isabel; Oarbeascoa, Gillen; et al.
Abstract: Chimeric antigen receptor (CAR) T cell–related HLH/MAS is an unusual manifestation of severe cytokine release syndrome (CRS) with poor prognosis and a challenging diagnosis. The establishment of specific diagnosis criteria is essential, and the combination of several techniques for CAR T‐cell follow‐up, allows a more precise management of this complication. Abstract : Cytokine release syndrome after CAR T‐cell therapy can evolve into CAR T cell–related HLH/MAS with high mortality and a challenging diagnosis. Combining different diagnosis techniques for CAR T‐cell follow‐up allows a more accurate diagnosis and targeted treatment.